Legal Protection of Minority Shareholders (Acquisition Company in Indonesia and Malaysia) - Sigit Somadiyono (Wajah Hukum, 2020)
The objective of research was to analyze the comparative legal provisions concerning the implementation regulation of the Legal Protection of Minority Shareholders in Context Acquisition Company in Indonesia and Malaysia. The journal is compiled with normative juridical research method with the approach of legislation, the conceptual approach and the approach of comparative law. Based on the survey results was revealed that basically the concept and criteria of legal protection of minority stockholders in the context of the acquisition of the same company. While suitability setting the position of trainee Shares Minority In Context Acquisition of Companies in Indonesia in accordance with the regulations but very difficult to implement because of the overlap with the rules above while in the Royal Malaysian implementation is very smooth due to the form of the rules in the form of legislation even though there are still gaps that need to be fixed in legislation there especially in the aspect that is still loose and often manipulated by the majority shareholders.